Cooperación intermunicipal: Revisión rápida de evidencia - Osvaldo Nina Baltazar; Daniela Berdeja (Institute for Advanced Development Studies (INESAD), 2021)
– The research carries out a systematic review to evaluate the necessary conditions that would allow inter-municipal cooperation to promote and generate positive impacts on the provision of public services. The strategy used for the review was the so-called rapid review of evidence, which allows systematizing the evidence on a public policy as exhaustively as possible, using it in a simplified way or omitting some steps of the systematic reviews. 65% of the 48 selected investigations were articles published in specialized journals and the rest were considered gray literature. The rapid review of evidence has shown that inter-municipal cooperation has achieved increased coverage and reduced costs, especially for small and medium-sized municipalities because they were more likely to benefit from cooperation. These achievements also depend on other factors, such as: the type of service, the management capacity of local authorities, the degree of decentralization and spatial proximity.
Keywords: H70; H77; O18; N36; R51; 330; Inter-municipal cooperation; local government; municipal association; public service provision; Latin America